2021
DOI: 10.18502/ohhp.v5i2.7013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Perceived Stress, Work-Family Conflict and Job Burnout in Nurses and Teachers in Bandar Abbas

Abstract: Introduction: Due to the great importance of health and various aspects of the duties and responsibilities of individuals in the nursing and teaching professions that can potentially be stressful for them. Therefore, the present study aimed to compare perceived stress, work-family conflict and job burnout in teachers and nurses in Bandar Abbas. Methods: The present study was descriptive and causal-comparative. The statistical population of the present study was all nurses and teachers in Bandar Abbas in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Factors such as variable work shifts, rotation, and discrepancies between nurses’ work holidays and official calendar holidays posed challenges, particularly for married nurses with children. Eyni’s study (2021)[ 20 ] found that rotational and variable nursing schedules can lead to more family functioning issues and work-related stress compared to other professions. Additionally, participants noted that individual behavioral characteristics, specifically conscientiousness, played a vital role in reducing MNC.…”
Section: Discussionmentioning
confidence: 99%
“…Factors such as variable work shifts, rotation, and discrepancies between nurses’ work holidays and official calendar holidays posed challenges, particularly for married nurses with children. Eyni’s study (2021)[ 20 ] found that rotational and variable nursing schedules can lead to more family functioning issues and work-related stress compared to other professions. Additionally, participants noted that individual behavioral characteristics, specifically conscientiousness, played a vital role in reducing MNC.…”
Section: Discussionmentioning
confidence: 99%